Criminological Analysis of Terrorism - Lasha Kukhianidze (European Scientific Journal, ESJ, 2016)
This article discusses the terrorism origin history, its types and forms, prevention issues and analysis of its concept from the historical and criminological aspects. The classification of the main features and elements of the terrorism is set out. The terrorism structure and methods of commitment of criminal acts are studied.